TRANSPARENCY METERS AND GAS ANALYZERS BASED ON TWO-WAVELENGTH SEMICONDUCTOR LASERS - V. L. Kozlov; M. M. Kygeiko (Приборы и методы измерений)
Construction techniques of precision measuring instruments of optical characteristics on the basis of two-wave lasers with use of basic and nephelometer methods are presented. System stability to changes of hardware constants, influence of an environment, pollution of optics is shown. The system automatically takes into account changes of a controllable line length that expands functionalities of a measuring instrument.